People in the mountains current approaches to the archaeology of mountainous landscapes - Pelisiak, Andrzej 1955-; Nowak, Marek ca. 20./21. Jh; Astaloş, Ciprian (Archaeopress Publishing, 2018)
Mountain landscapes were first exploited by farming populations at the very beginning of the Neolithic. However, there are controversies regarding when and where these specific types of human behaviour developed as a result of adaptation processes to these special environments. The aim of this book is to present research results from different scientific contexts. To discuss these issues, and to study different aspects of human activity in the mountains and adjacent regions we incorporate archaeological, botanical, zooarchaeological and ethnological information
Introduction: "... The inspiration for this volume came from papers presented during a session entitled People and the mountains – entering into the new landscapes, organised in 2014 by Andrzej Pelisiak (Institute of Archaeology, University of Rzeszów, Poland), Marek Nowak (Institute of Archaeology, Jagiellonian University, Kraków, Poland) and Ciprian Astaloş (Satu Mare County Museum, Satu Mare, Romania) within the frameworks of the 20th Annual Meeting of the European Association of Archaeologists in Istanbul...
Keywords: Excavations (Archaeology); Mountains; Antiquities, Prehistoric; Gebirge; Archäologie; Konferenzschrift; Aufsatzsammlung